2015
DOI: 10.1055/s-0035-1558406
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Localization of the Monro Foramen and the Safest Stereotactic Interforniceal Approach to the Third Ventricle: A Neuroanatomical Study

Abstract: The present study shows how neurosurgeons can localize and use crucial anatomical landmarks, namely the AC and foramen of Monro, to approach the third ventricle safely via a stereotactic interforniceal technique. This can be achieved during preoperative planning with simple identification of stereotactic points A, B, and M on preoperative median sagittal magnetic resonance images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previously we used 26 adult cadaveric brains and 200 adult brain MRIs describing the third ventricle floor and related structures and concluded that, in older subjects and when the basilar artery caliber was larger, its apex was closer to the floor of the third ventricle [ 5 ]. Mavridis and Anagnostopoulou described the stereotactic localization of the anterior-inferior border of the IVF and the midpoint between it and the anterior commissure, using 44 cadaveric hemispheres to define a safer approach to the third ventricle [ 15 ]. Using the posterosuperior border of the anterior commissure as the stereotactic reference point, these authors found that the mean stereotactic Y coordinate of the IVF anterior-inferior border was -0.61 ± 1.58 mm and the mean stereotactic Z coordinate for the same point was 2.41 ± 2.93 mm [ 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we used 26 adult cadaveric brains and 200 adult brain MRIs describing the third ventricle floor and related structures and concluded that, in older subjects and when the basilar artery caliber was larger, its apex was closer to the floor of the third ventricle [ 5 ]. Mavridis and Anagnostopoulou described the stereotactic localization of the anterior-inferior border of the IVF and the midpoint between it and the anterior commissure, using 44 cadaveric hemispheres to define a safer approach to the third ventricle [ 15 ]. Using the posterosuperior border of the anterior commissure as the stereotactic reference point, these authors found that the mean stereotactic Y coordinate of the IVF anterior-inferior border was -0.61 ± 1.58 mm and the mean stereotactic Z coordinate for the same point was 2.41 ± 2.93 mm [ 15 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mavridis and Anagnostopoulou described the stereotactic localization of the anterior-inferior border of the IVF and the midpoint between it and the anterior commissure, using 44 cadaveric hemispheres to define a safer approach to the third ventricle [ 15 ]. Using the posterosuperior border of the anterior commissure as the stereotactic reference point, these authors found that the mean stereotactic Y coordinate of the IVF anterior-inferior border was -0.61 ± 1.58 mm and the mean stereotactic Z coordinate for the same point was 2.41 ± 2.93 mm [ 15 , 20 ]. Comparing these measurements with the present results (mean ± SD: Y = − 1.92 ± 0.779 mm; Z = 3.94 ± 1.175 mm), it was found that the anterior border of the IVF seems to be placed slightly more posteriorly and superiorly, but the difference does not appear to be significantly different.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations